Going the Extra Mile: What Drives Employee Voluntarism in Public Sector Organizations? - Saud, Jenna; Rice, John Lewis (International Review of Management and Marketing, 2024)
This research intends to investigate the impact of employee age and innovative work climate on the relationship between supportive supervisory roles and employee acts of voluntarism. Using a large cross-sectional survey of the Australian Public Service we find that the influence of supportive supervisors on employees’ acts of voluntarism and extra role behaviors at work is higher amongst younger employees. This indicates that younger employees are more likely to engage in acts of voluntarism as a result of supportive supervisory roles. Findings also indicate that innovative work climate accentuates the relationship between supportive supervisory behaviors and acts of voluntarism. Employees who experience high levels of innovative work climate and high levels of support from supervisors tend to display higher levels of voluntarism and extra role behaviors at work. These findings have several theoretical and practical implications.